Hubungan Antara Pola Asuh Orang Tua dengan Kecerdasan Emosional (Emotional Intelligence) Siswa Kelas V SDN 50 Kota Bengkulu - Enda Yulita; Herman Lusa; Sri Dadi (Universitas Bengkulu, 2018)
This research aims to determine the relationship between parenting style with the emotional intelligence of class V at SDN 50 Bengkulu City. This type of research is quantitative with correlational research methods. The study population was all students of class V SDN 50 Bengkulu City, as many as 40 people. The study samples was all population. Data collection techniques in this study using questionnaires. Data were analyzed using correlation test Product Moment and t test. The results showed that there is a significance relationship between parenting style with the emotional intelligence of class V at SDN 50 Bengkulu City. This is evidenced by rhitung is greater than rtabel (0,618 ? 0,312), with contributed variable X for variable Y 38,19%, and thitung is greater than ttabel (4,294 ? 1,685) at significance level of 5%.